Pits and boots : excavation of medieval and post-medieval backlands under the Bon Accord Centre, Aberdeen - Roy, Michael (Archaeopress Archaeology, 2021)
Excavations in 2007-8, ahead of an extension to the Bon Accord Centre in Aberdeen, uncovered backlands that would have formed part of the industrial quarter of the medieval town. The excavation charts the changing nature of the area, from an industrial zone in the medieval period, to horticultural and domestic spaces in post-medieval times.